2022
DOI: 10.1038/s41419-022-05195-9
|View full text |Cite
|
Sign up to set email alerts
|

A dual role of lola in Drosophila ovary development: regulating stem cell niche establishment and repressing apoptosis

Abstract: In Drosophila ovary, niche is composed of somatic cells, including terminal filament cells (TFCs), cap cells (CCs) and escort cells (ECs), which provide extrinsic signals to maintain stem cell renewal or initiate cell differentiation. Niche establishment begins in larval stages when terminal filaments (TFs) are formed, but the underlying mechanism for the development of TFs remains largely unknown. Here we report that transcription factor longitudinals lacking (Lola) is essential for ovary morphogenesis. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The w 1118 and C587‐Gal4 fly lines (Zhao et al. , 2022) were maintained in the laboratory. The Ptc‐Gal4 (THJ0201), Nos‐Gal4 (TB00040), UAS‐CG3526 RNAi (TH04130.N), and UAS‐Stat92E RNAi (THU0573) fly lines were obtained from Tsinghua Fly Center in Beijing, China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The w 1118 and C587‐Gal4 fly lines (Zhao et al. , 2022) were maintained in the laboratory. The Ptc‐Gal4 (THJ0201), Nos‐Gal4 (TB00040), UAS‐CG3526 RNAi (TH04130.N), and UAS‐Stat92E RNAi (THU0573) fly lines were obtained from Tsinghua Fly Center in Beijing, China.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted as described previously (Zhao et al. , 2022). The 1 st ‐strand cDNA was synthesized from 1 μg of total RNA using HiFiScript gDNA removal cDNA Synthesis Kit (Cwbiotech, Taizhou, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al reported that lola is also essential for TF formation. In lola RNAi ovaries, either no TF stacks are formed or they are disordered [50]. Coincidentally, both lola and bab/ bab2 have a BTB domain, suggesting that this domain may be necessary for TF formation.…”
Section: Pathways That Regulate Tfc Formationmentioning
confidence: 99%
“…In addition to these signaling pathways, a few genes, including twinstar (tsr), bric-à-brac (bab1/bab2), LIM homeobox transcription factor 1 alpha (Lmx1a) and longitudinals lacking (lola), have been reported to be involved in TFC formation [46][47][48][49][50]. Chen et al found that in tsr mutant ovaries, the TFC number decreased and all TFCs have a rounded appearance.…”
Section: Pathways That Regulate Tfc Formationmentioning
confidence: 99%